Implementation of a Healthy Living Culture through the Healthy Community Movement Program (GERMAS) in Sumberasih District: Implementasi Budaya Hidup Sehat Melalui Program Gerakan Masyarakat Sehat (GERMAS) Di Kecamatan Sumberasih - Vivin Ary Syabella; Veren Myvara; M. Khoirul Zacky; Ananta Prathama (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
GERMAS was designed by the President of the Republic of Indonesia to increase public awareness regarding the importance of a healthy lifestyle as a preventive measure in maintaining health and preventing disease. This activity was carried out to determine the implementation of the GERMAS program in Sumberasih District. The method used is a qualitative method implemented in Edward III implementation-based activities, covering 4 aspects, namely Communication, Resources, Disposition and Bureaucratic Structure. Activities are carried out in the form of interviews, observations and documentation. The results obtained indicate that the implementation of the GERMAS program in Sumberasih District is already underway and is still developing. One of the activities is in the form of outreach and outreach by stakeholders and posyandu cadres. The service team is actively involved in these activities. The community is required to be more massive in implementing healthy living behavior so that this program runs more optimally. The results of the activities show that the implementation of the GERMAS program in Sumberasih District was carried out to empower the community to improve, protect and maintain their health conditions. People become aware and motivated to contribute proactively in improving and maintaining their own health conditions.